EVALUATION ON COMMUNITY BASED FOREST MANAGEMENT IMPLEMENTATION IN RANDUBLATUNG, BLORA - Susilowati, Indah; Esariti, Landung (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Community Based Forest Management (CBFM) program is implemented so that forest resource benefit and management can be functioned according to optimal and proportional contribution. Randublatung  forest  in Blora  Regency  represents  forest  area  region  applying  the  CBFM program. Due to constraints in CBFM implementation and policy in Randublatung, an evaluation study is conducted, and Jegong village is chosen as a sample area. The mix approach using less quantitative more qualitative method  is depicted to describe the phenomenon and justify the reasons behind the situation. Evaluation is conducted using four important aspects namely CBFM management, sharing procedure, implementation stages and institutional system. Result shows  that  CBFM  implementation  in  Jegong  village  is  suitable,  although  it  is  found some constraint in the implementation process. To conclude, four strategies are created to respond for better application of CBFM Randublatung. There are developing the implementation stages in  CBFM, institutional  development  strategy,  multistakeholders  collaboration  strategy  and sharing contribution strategy.